Strategi Guru Akidah Akhlak dalam Pembentukan Nilai Keagamaan pada Peserta Didik MAN 4 Jombang - Hurier, Binti Luthfiya; Maunah, Binti (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2023)
This study offers a comprehensive exploration of how educational strategies can influence the character and attitudes of students from MAN 4 Jombang, facilitating the integration of religious values into their everyday lives. The research approach employed is qualitative in nature, falling under the category of field research. The data collection procedures encompass in-depth interviews, participant observation, and documentation. Data analysis involves three concurrent processes: data reduction, data presentation, and drawing conclusions. The findings indicate that the pedagogical approaches adopted by Aqidah Akhlak teachers to impart religious values to students at MAN 4 Jombang encompass tawādu' (humility), tasāmuḥ (tolerance), and ta'āwun (cooperation) attitudes. These are enacted through a range of methodologies, including Contextual Teaching and Learning (CTL), inquiry-based learning, problem-based learning, cooperative learning, and affective teaching. The utilization of habituation techniques and direct engagement in social interactions aids in the assimilation of religious principles into the students' daily routines. The teacher's dual role as both a living model and a facilitator in applying these principles assumes a pivotal position within this process. The implications of these findings extend beyond individual students, significantly impacting broader society.